Frente a negras pasiones… una pasión negra: claves para entender la vigencia del pensamiento (afro) latinoamericanista de Juan Montalvo - Miranda, Franklin (2024)
The author rethinks some of the cultural proposals in Montalvo’s essays. He begins by defending the characteristic of the controversy as an esthetic and ethical tool: he employs it with a literary zeal –in much the same style as Sarmiento, González Prada among others– and also as a writer linked to militant politics to encourage a not so very educated audience. In his thinking, he points out the oscillations between pro-European, Hispano-Americanist and Latin- Americanist ideas. There are coincidences between Montalvo and Pedro Henríquez Ureña on considering what is referred to as Latin American; their thinking moves between that which is considered national and of the popular subject (links with Martí and Bello). The author considers the nation as a corporate totality, in an anti-colonial proposal of republican character: where the freedom of opinion, fraternity and democracy would have prevailed. He analyzes Montalvo’s ideas about the popular masses, emphasizing the humanist trait in the meaning of civilization and barbarism (that would be the opposite to peace which is obtained by respect and not by fear of political leaders or of the church); Montalvo advocates the creation of a virtuous people as a result of work and a balance between reason and pleasures; he justifies the need for popular illustration and that a hero guides the people (not enslave them); nevertheless, on meaningfully defining the social classes he does not consider notions of cast. On referring to the Afro people, he again maintains that it is slavery, which places them in an inferior position, insisting in the non- existence of innate inferiority.